2019
DOI: 10.1002/anie.201813744
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Topographical Single‐Cell Imaging by Near‐Field Desorption Mass Spectrometry

Abstract: Simultaneously acquiring chemical and topographical information within asingle cell at nanoscale resolutions is vital to cellular biology,yet it remains agreat challenge due to limited lateral resolutions and detection sensitivities.H erein, the development of near-field desorption mass spectrometry for correlated chemical and topographical imaging is reported, therebyb ridging the gap between laser-based mass spectrometry (MS) methods and multimodal single-cell imaging.Using this integrated platform, an imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 42 publications
0
64
0
Order By: Relevance
“…Low‐micrometer‐resolution and high‐throughput studies have been demonstrated with a microscope mode MSI . Near‐field‐based MSI techniques have reportedly achieved a lateral resolution of 350 nm for intact molecules and 50 nm for elements, respectively . Recently, a technique that combines transmission‐mode MALDI and post‐ionization was used to successfully image tissue and cell samples on a scale of approximately one micrometer .…”
Section: Introductionmentioning
confidence: 99%
“…Low‐micrometer‐resolution and high‐throughput studies have been demonstrated with a microscope mode MSI . Near‐field‐based MSI techniques have reportedly achieved a lateral resolution of 350 nm for intact molecules and 50 nm for elements, respectively . Recently, a technique that combines transmission‐mode MALDI and post‐ionization was used to successfully image tissue and cell samples on a scale of approximately one micrometer .…”
Section: Introductionmentioning
confidence: 99%
“…Although the above techniques effectively advance the applications of laser‐based mass spectrometry in fields concerned with the microscale, most of the techniques are quite complex and expensive to implement in most laboratories, which is one of the reasons for the slow development of single‐cell MSI. Although it is possible to visually detect lipids and drugs at the cellular level, the study of the spatiotemporal distribution rules of drugs within the organelles by laser mass spectrometry, which is key to revealing the mechanism of inducing apoptosis of in cancer cells, is still in the early stages due to the limited lateral resolution and detection sensitivity of these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we demonstrate a nano laser probe (NLP)‐based laser desorption ionization (LDI) mass spectrometry imaging method by introducing the sampling laser with a single‐mode micro‐lensed fiber. Compared with our previous near‐field desorption technique, the new method has been greatly improved in operability and universality. By eliminating the need for complex AFM systems, this new nanoscale resolution imaging technology is much more compatible with existing laser mass spectrometers.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed ionization methodology is a good choice in this case and it can even realize ultra-microanalysis of solution and solid samples. [39][40][41] Another practical way to reduce sample consumption in routine MS analysis is self-aspirating sampling, namely, gaseous or liquid samples are directly drawn to the ion source with minimal residual during the sampling process. [33][34][35][42][43][44] This approach can endue the mass spectrometer with sniffing ability similar to the olfaction of animals to detect volatile mixtures, 44 but additional pump or assistant gas ow are commonly needed to create the inspiration channel to drive the sample introduction.…”
Section: Introductionmentioning
confidence: 99%